2020
DOI: 10.1029/2019sw002330
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Scale Index Map Based on TEC Data During the Saint Patrick Magnetic Storm and EPBs

Abstract: This study examines the variability of the ionospheric content during the period around the 2015 Saint Patrick magnetic storm and when equatorial plasma bubbles (EPBs) are observed during the quiet time over South America during two other events. It uses the ionospheric scales index map based on the disturbance ionospheric index (DIX). The results are compared to the traces of the ionograms obtained at three different ionospheric stations (Fortaleza, Campo Grande, and Cachoeira Paulista) in Brazil acquired in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…However, as the irregularities start to develop spread F in the CAJ2M ionograms (03:50 to 06:50 UT), we can see a gradual increase in DIX, which reaches a peak at 06:50 UT. This feature reinforces that the DIX is strongly related to the physical variations in the ionosphere that are measured by the ionosonde (Denardini et al, 2020b).…”
Section: Analysis Of Epb-related Ionospheric Disturbances Under Low S...supporting
confidence: 81%
See 1 more Smart Citation
“…However, as the irregularities start to develop spread F in the CAJ2M ionograms (03:50 to 06:50 UT), we can see a gradual increase in DIX, which reaches a peak at 06:50 UT. This feature reinforces that the DIX is strongly related to the physical variations in the ionosphere that are measured by the ionosonde (Denardini et al, 2020b).…”
Section: Analysis Of Epb-related Ionospheric Disturbances Under Low S...supporting
confidence: 81%
“…Moreover, the authors discussed the DIX response to pre-storm effects and other phenomena, such as sporadic E layers. Denardini et al (2020b) analyzed DIX maps calculated for South America during extreme geomagnetic storms and plasma bubbles. Besides the magnetic storm analysis, the authors associated local disturbances in DIX with the equatorial spread F (ESF) observed over the same area of study.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this work is the evolution of the plasma bubbles generated in the recovery phase of this storm. Other perturbations during this storm have been studied by several authors (e.g., Astafyeva et al, 2015;Denardini et al, 2020;Kuai et al, 2016;Venkatesh et al, 2017;Verkhoglyadova et al, 2016;Zhang et al, 2017). These EPBs structures were so intense that even with sunrise and photoionization effects active were not enough for these structures to cease.…”
Section: Discussionmentioning
confidence: 92%
“…The ionospheric response to the St. Patrick's Day magnetic storm (17–18 March 2015) has been analyzed in many studies (e.g., Astafyeva et al., 2015; Denardini et al., 2020; Fagundes et al., 2016; Figueiredo et al., 2017; Venkatesh et al., 2017). However, in‐depth analyses of pre‐ and post‐sunrise plasma bubbles generated during the St. Patrick's geomagnetic storm in the South American sector have not been reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation